Factors Affecting Participants’ Knowledge-Sharing Behaviors in Online Communities: a Systematic Review - Sari, Hasan; Othman, Marini (International Journal of Engineering and Technology, 2018)
In the current competitive economy, knowledge considered as a valuable source of competitive advantage. Online Communities (OCs) became accepted online popular platforms for exchanging and sharing knowledge between groups or individuals with common needs and interest. How to motivate users to contribute their knowledge is one of the most challenges in OCs. The factors that influence members to exchange their knowledge in OCs have not fully explored in the context of knowledge sharing. This systematic literature review aimed to examine the previous quantitative/qualitative studies from 2006 to 2017 to identify the most frequently cited factors that influence participants’ knowledge sharing behavior in OCs. The current study classified those factors into three main categories: individual, community, and technological factors. The study also examined different theories, constructs, and models that used in the selected articles. The findings from this study could be applied in future empirical research to construct a conceptual framework for members’ knowledge sharing behavior in OCs.